Impact of Training and Development on Employee Performance in Abubakar Tatari Ali Polytechnic (ATAP) Bauchi, Bauchi State, Nigeria - Aliyu, Mohammed Resheed; Bello, Hashim Sabo; Bello, Mansur (NIU Journal of Humanities, 2018)
The focus of this study is to determine the impact of training and development on employees’ performance in Abubakar Tatari Ali Polytechnic Bauchi. The study determined the level of T&D in Abubakar Tatari Ali Polytechnic, Bauchi. Determine the level of employee performance in Abubakar Tatari Ali Polytechnic, Bauchi. And also determine the relationship between training and development and employee performance in ATAP, Bauchi. Training and development presents a prime opportunity to expand the knowledge base of all employees but many employers find the development opportunities expensive. The research employed quantitative approach. The data were collected through structured questionnaire, developed by the researchers. The study involved 201 samples of academic and senior nonacademic staff of the polytechnic. The data was analyzed using Pearson’s linear correlation coefficient and hypotheses were tested using correlation coefficient. The result of the study is expected to be beneficial to the institution, the state in formulating training and development programs, and entire nation in designing proactive and technical measures for addressing employee performance problems. The finding proved that training and development have strong relationship with employee performance in ATAP Bauchi. T&D serve as major factors that enhance employee performance and productivity. The study recommends that employee needs should be considered in designing training and development programme. The institution should improve on T&D investment to make employees compete favorably with global edge. The study also recommends that employees should be given chance to acquire new skills and abilities toward developing the habit of commitment in discharging their responsibilities. Keywords : Training and Development, Knowledge and Skills Acquired, Employee Performance